Japan-Us Relations After World War Ii: From the Occupation Regime to the Recapture of Okinawa by Japan (Texas Journal of Multidisciplinary Studies, 2022)
After World War II approach of Japan and the US, being withdrawn of the war in Japanese legislation and diplomatic relations, in 1970s Japanese disposal from the US leading occupation regime due to the right strategy chosen by Japan.